Remarks on Zasada efektywności w prawie międzynarodowym [Principle of effectiveness in international law] by Janusz Symonides: On the Anniversary of the Conclusion of the Polish-German Treaties of 1950, 1970 and 1990 (Polish Yearbook of International Law, 2021)
The present article combines some reflections on the late Prof. Janusz Symonides’ most interesting book on the concept and role of effectiveness in international law (Zasada efektywności w prawie międzynarodowym, UMK, Toruń: 1967), with reflection over the anniversaries of the most important Polish-German treaties which not only constituted the basis for bilateral relations between Poland and Germany, but were also of importance for East-West relations. The analysis that follows deals mostly with the significance of effectiveness in the context of boundaries and their recognition, as well as with nationality. The article shows that most of the concepts and ideas of Prof. Symonides still remain actual today.